Al-Barr Verse 177 from Surat Al-Baqara - An Analytical Study - - Ali , Saadi (Islamic Sciences Journal, 2023)
Among the generous verses in which there is abundant goodness and guidance is a great verse of righteousness (177) from Surat Al-Baqara, as it contains a clear statement, complete guidance to the believer and his duties and obedience until he reaches the connection of righteousness in which victory and prosperity, as the verse began with a remembrance of faith in Allah and the Day ; Because they are the basis of all righteousness, and the principle of all that is good, and is not already full of faith to righteousness unless the master of self dominated them with an evidence, and accompanied by submission and acquiescence, and a factor with all the things that hypothesized and guided by Allah the Almighty - of the duties and virtues of that upgrade the believer to the degree of goodness and acceptance . I have studied and analyzed this blessed verse within the steps of analytical interpretation, relying in its study on the various books of interpretation, and important linguistic dictionaries to reach the most important aspects of the verse concerning in the guidance, meanings, and values and written a research entitled (verse 177 of Surat Al-Baqarah - analytical study). Our final prayer is: Praise be to Allah, Lord of the worlds, and may blessings and peace be upon the faithful Prophet and his family and companions.